2004
DOI: 10.1002/jrs.1125
|View full text |Cite
|
Sign up to set email alerts
|

In situ laser‐induced formation of α‐Fe2O3 from Fe3+ ions in a cylindrical core‐shell polymer brush

Abstract: The Raman spectrum of a cylindrical core-shell polymer brush containing Fe 3+ ions was measured in a confocal spectrometer equipped with an He-Ne laser. During irradiation, the polymer matrix decomposed, and carbonaceous compounds containing sp 2 and sp 3 hybridized carbon were formed. Simultaneously, the strong and narrow Raman lines of crystalline a-Fe 2 O 3 (hematite) began to show up in the spectrum. After prolonged irradiation, the carbon signals decreased, whereas the hematite peaks remained strong. Simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…6), the BE of O 1s (529.7 eV) and Fe 2p (710.8 eV) were lowered as compared to those of S1. Generally Co 2p 3/2 was observed at 780 eV for CoO [50], but we have found the same spectra at 780.2 eV. The shifting again confirms the substituition of Co and there is formation of its mixed oxide.…”
Section: Xpssupporting
confidence: 86%
“…6), the BE of O 1s (529.7 eV) and Fe 2p (710.8 eV) were lowered as compared to those of S1. Generally Co 2p 3/2 was observed at 780 eV for CoO [50], but we have found the same spectra at 780.2 eV. The shifting again confirms the substituition of Co and there is formation of its mixed oxide.…”
Section: Xpssupporting
confidence: 86%
“…According to Weber et al the first peak is due to F 2g mode of the ceria cubic lattice (Weber et al, 1993). Similarly for Fe 2 O 3, three bands were observed at 282 and 1067 cm -1 for hematite and 713 cm -1 is for maghemite (Leon et al, 2004). Shifting of peaks by some units from their original value of parent material from references, ascertains the formation of mixed oxide between Fe 2 O 3 and CeO 2 .…”
Section: Raman Spectra Studymentioning
confidence: 87%
“…Previous studies (Bersani et al, 2000;Zoppi et al, 2010) showed that the bands appearing at 220, 290, 403, 500, 609, 650 cm -1 were commonly assigned to hematite. However, the band at 650 cm -1 is usually a low-intensity signal and the literature (León et al, 2004) reported that it was not the spectrum of a perfect hematite due to the lack of longrange order. On the other hand, earlier work (Buciuman et al, 1999;Hong et al, 2011) confirmed that the Raman spectrum of the MnO 2 appear in the range of 580-650 cm -1 .…”
Section: Ramanmentioning
confidence: 99%